Study of the physical properties of ZnS thin films deposited by RF sputtering. (15th November 2017) - Le Donne, A.; Cavalcoli, D.; Mereu, R.A.; Perani, M.; Pagani, L.; Acciarri, M.; Binetti, S.
Abstract: ZnS is a versatile, abundant and eco-friendly semiconductor material employed in many applications. In the present manuscript, ZnS thin films were grown by one of the most simple and scalable vacuum method, that is the room temperature radio frequency sputtering technique. An extensive characterization has been performed by atomic force microscopy, X-ray diffraction, absorption and photoluminescence spectroscopies to identify the growth conditions required to obtain compact and low- defective ZnS layers, as required in many applications. Optimized thin films consist of nanocrystalline ZnS with very low surface roughness with respect to the literature, which make them particularly suitable for optical interfacing and alternative buffer layer in chalcogenide thin film solar cells.